The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/jez.b.22499
|View full text |Cite
|
Sign up to set email alerts
|

Polyploidy Is Genetic Hence May Cause Non‐Adaptive Radiations, Whereas Pseudopolyploidy Is Genomic Hence May Cause Adaptive Non‐Radiations

Abstract: There are two ways eukaryotes double number of chromosomes: (1) whole genome duplication (polyploidy), in which all nuclear DNA is replicated, and (2) karyotypic fission (pseudopolyploidy), in which all chromosomes are physically bifurcated. We contrast polyploidy with pseudopolyploidy, highlighting when it is crucial to look at genetic vs. genomic levels. We review history of pseudopolyploidy, including recent mechanisms by which chromosomal bifurcation may occur and outline methods for detecting such genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…There are also arguments for polyploids not contributing to adaptive radiations per se , but rather polyploids simply arising through their immediate reproductive isolation from parental lineages (purely as a result of differences in chromosome number). Where recurrent polyploidization occurs between the same or different parental species, (non‐adaptive) radiations can result (Gorelick & Olson, ). Even if neopolyploids do have higher extinction rates and make a lower contribution to recent species diversification, as has been argued, all angiosperm species nonetheless have (often multiple rounds of) polyploidy in their ancestry; the ramifications of this are significant and an important focus of research.…”
Section: Evolutionary Dynamics Of Polyploidsmentioning
confidence: 99%
“…There are also arguments for polyploids not contributing to adaptive radiations per se , but rather polyploids simply arising through their immediate reproductive isolation from parental lineages (purely as a result of differences in chromosome number). Where recurrent polyploidization occurs between the same or different parental species, (non‐adaptive) radiations can result (Gorelick & Olson, ). Even if neopolyploids do have higher extinction rates and make a lower contribution to recent species diversification, as has been argued, all angiosperm species nonetheless have (often multiple rounds of) polyploidy in their ancestry; the ramifications of this are significant and an important focus of research.…”
Section: Evolutionary Dynamics Of Polyploidsmentioning
confidence: 99%
“…This extraordinary diversity in the DNA amount is not entirely dependent on the number of genes or overall organism complexity (e.g., Gregory, 2001), but can be mostly attributed to differences in repetitive DNA, especially, to transposable elements (Sanmiguel and Bennetzen, 1998; Hawkins et al, 2006). It has been shown that a substantial part of the AGS variability in plants is linked with variation in chromosome numbers, the number of polyploidization events or less dramatic changes such as rearrangements of existing chromosomes (e.g., Leitch and Bennett, 1997, 2004; Otto and Whitton, 2000; Bennetzen et al, 2005; Gorelick and Olson, 2013). Multiple recent studies point out that although AGS initially increases through whole‐genome duplication or accumulation of transposable elements, these processes are usually followed by genome downsizing by means of deletion of transposable elements, illegitimate recombination, or removal of large blocks of DNA (Sanmiguel and Bennetzen, 1998; Hawkins et al, 2006; Vitte and Bennetzen, 2006; Ross‐Ibarra, 2007; Tiley and Burleigh, 2015).…”
mentioning
confidence: 99%
“…Double the nuclear genome size via polyploidy (i.e. whole genome duplication; see Gorelick & Olson, ) and the nucleus will be roughly twice the volume. Polyploid cells are larger than their diploid progenitors (Lomax et al ., ).…”
mentioning
confidence: 99%